Long-term trends in the abundance and breeding performance in Adélie penguins: the Argentine Ecosystem Monitoring Program - Juares, Mariana Alejandra; Silvestro, Anahí Mariel; Alfonso, Brenda C.; Santos, Maria Mercedes
In this work, we report long-term trends in the abundance and breeding performance of Adélie penguins (Pygoscelis adeliae) nesting in three Antarctic colonies (i.e., at Martin Point, South Orkneys Islands; Stranger Point/Cabo Funes, South Shetland Islands; and Esperanza/Hope Bay in the Antarctic Peninsula) from 1995/96 to 2022/23. Using yearly count data of breeding groups selected, we observed a decline in the number of breeding pairs and chicks in crèche at all colonies studied. However, the magnitude of change was higher at Stranger Point than that in the remaining colonies. Moreover, the index of breeding success, which was calculated as the ratio of chicks in crèche to breeding pairs, exhibited no apparent trend throughout the study period. However, it displayed greater variability at Martin Point compared to the other two colonies under investigation. Although the number of chicks in crèche of Adélie penguins showed a declining pattern, the average breeding performance was similar to that reported in gentoo penguin colonies, specifically, those undergoing a population increase (even in sympatric colonies facing similar local conditions). Consequently, it is plausible to assume a reduction of the over-winter survival as a likely cause of the declining trend observed, at least in the Stranger Point and Esperanza colonies. However, we cannot rule out local effects during the breeding season affecting the Adélie population of Martin Point. Fil: Juares, Mariana Alejandra. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Silvestro, Anahí Mariel. Universidad Nacional de Luján. Instituto de Ecología y Desarrollo Sustentable. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Ecología y ...